Music by Reena Esmail, Faculty Artists Recital - McLaughlin Large, Karen; B. Parker, Craig; Arrington, Amanda; Johnson, Jim; Fassler-Kerstetter, Jacqueline; Hunt, Paul; Maxwell, Steve; Thompson, Patricia; Morris, Alyssa; Littrell, David; Brokenicky, Janie (Kansas State University, School of Music, Theater, and Dance, 2018)
Faculty Artist Recital - Music by Reena Esmail Wednesday, November 29th, 2017 7:30p.m. All-Faiths Chapel Auditorium Karen McLaughlin Large, flute Alyssa Morris, English horn Craig B. Parker, trumpet Jim Johnson, trumpet Jacqueline Fassler-Kerstetter, horn Paul Hunt, trombone Steve Maxwell, tuba Amanda Arrington, piano David Littrell, cello Janie Brokenicky, conductor